Organizational Culture: Case of the Finnish Construction Industry (Construction Economics and Building, 2018)
Academic literature has long recognized the correlation between a company’s organizational culture and its quality performance. The Finnish construction industry is still a highly human powered industry, and thus, organizational culture is seen to have a significant effect on an organization’s efficiency as well. The aim of this study is to examine and determine organizational cultural profiles of organizations in the Finnish construction industry as they are currently perceived and preferred by professionals themselves. In all, 121 professionals working in organizations in the Finnish construction industry were surveyed using the Organizational Culture Assessment Instrument (OCAI). The reliability of characteristics was tested by calculating Cronbach alpha reliability coefficients, and the found differences between the response characteristics were analysed in-depth with paired and independent t-test analyses. The findings show that, on average, construction industry organizations in Finland currently operate with a mixture of clan and hierarchy cultures. Thus, the current organizational culture stresses the point of view of internal focus and integration. However, the organizations desired to emphasize more flexibility and discretion toward individuals. The novelty value of this paper is presenting existing and preferred culture profiles in the Finnish construction industry. These found profiles have the potential to improve management of organizations, which results in better efficiency of the industry through better performance of organizations in the construction industry.